Islamic ethics and guidelines for using facebook: a maqasidic analysis - Amanullah, Muhammad (2015)
“Facebook is a popular free social networking website that allows registered users to create profiles, upload photos and videos, send messages and keep in touch with friends, family and colleagues.”1 It is considered to be one of the latest types of social media, which is now being used by approximately one and half billion people all over the world. This website has many advantages as well as many disadvantages. Because of its disadvantages many problems have been occurring among its Muslim as well as non-Muslim users all over the world. In order to overcome these problems, comprehensive ethical guidelines are urgently required. Efforts have already been undertaken to counter some of these problems by the developers, who have tried to create some systems and regulations to be followed by its users, and likewise, some non-Muslim scholars have also tried to produce some ethical guidelines for using this website. However, these are not sufficient for Muslim users. Some Muslim scholars have also tried to develop some Islamic guidelines and ethics for using it, but according to his knowledge and search, the present researcher could not find comprehensive Islamic ethical guidelines for using Facebook. Therefore, using descriptive and analytical methods and based on certain verses of the Qur’an and ahadith of the Prophet (p. b. u. h.), the researcher aims to produce comprehensive Islamic ethics and guidelines for the users of Facebook. Additionally, he conducts a maqasidiq analysis of all components of this research. There are five/six higher maqasid or objectives of Islamic Shari`ah, i.e. protection of religion (hifz aldin), protection of life (hifz al-Nafs), protection of intellect (hifz al-`aql), protection of property (hifz al-mal), protection of progeny (hifz al-nasl), and protection of honor and prestige (hifz al-`ird).2 The researcher strives to relate different parts of this article with these objectives. By and large, this research does not touch upon the Islamic ethics and guidelines for the developers of this website. This research is divided into following sections: introduction, advantages of using Facebook, disadvantages of using it, Islamic ethics and guidelines for using it, conclusion and suggestions.